Mampukah Model Problem Based Learning meningkatkan Prestasi Belajar Sains Mahasiswa Calon Guru Sekolah Dasar? - Yanti Fitria (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
This study aims to improve the learning achievement of elementary school students. Second semester students majoring in elementary school teacher education (PGSD) FIP UNP Padang were involved as research subjects. As many as 24 students were given science learning by using the Problem Based Learning model. Subjects/samples of the study were given learning actions in the lectures of the basic concepts of Natural Sciences. Data obtained after the study were analyzed with descriptive statistics. This research was a classroom action research and was carried out for two cycles. The research findings show the results that an increase in student learning achievement with an average achievement score in cycle one of 76.28 and an average score in the second cycle of 88.46. An increase in score of 86.75. The findings can be concluded that the Problem Based Learning model is effective in improving student learning achievement rather than independent learning. Thus the science learning model Problem Based Learning can be used as an alternative model to improve student achievement in the digestive system material.